THE VILLA, IDENTITY COMPONENT IN THE TOURISM INFRASTRUCTURE OF BORSEC SPA RESORT - G. B. TOFAN; A. NIŢĂ (Studia Universitatis Babeş-Bolyai: Geographia, 2018)
Our study intends to emphasize several trends concerning the dynamic of a classic accommodation component (villa), currently experiencing a revival and rehabilitation in Borsec. In regards to this last aspect, one must point out that most investors are from the Republic of Moldova, Hungary and Israel. In Borsec, this form of accommodation was dominant at the beginning of the 1990s, but due to severe wear and tear and gradual closures, the accommodation structure began to change in 2004, villas being slowly replaced by tourist pensions. This situation was further exacerbated by difficult road and railway connections, traffic requiring transhipment. The closest railway station is in the town of Topliţa, 25 km away, while the Târgu Mureş “Transylvania” International Airport is located roughly 140 km away. In the last couple of years, a lot of attention was focused on county road 128 (Borsec-Jolotca), since it is an investment crucial for the tourists visiting Borsec, by shortening the distance by 30 km to the county capital, Miercurea-Ciuc. Another noteworthy aspect is that in February 2017, the Government Decree no. 9 restated the town of Borsec as a national tourism resort.